2019
DOI: 10.47176/mjiri.33.153
|View full text |Cite
|
Sign up to set email alerts
|

The bactericidal effect of liposomal vancomycin as a topical combating system against Methicillin-resistant Staphylococcus aureus skin wound infection in mice

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common causes of skin infections and treatment is difficult due to its resistance to the most of antibiotics. Although vancomycin is often considered as an antibacterial agent of choice for the treatment of MRSA, its use is limited because of the high side effects. One solution is using liposomal formulation for local drug delivery. The aim of this study was to determine in vitro and in vivo efficacies of liposomal vancomycin as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Vancomycin formulated as nanoplexes of the antibiotic with dextran sulfate sodium salt has recently addressed MRSA infections; the size, polydispersity, and zeta potential of the optimized nanoplexes were 84.6 ± 4.3 nm, 0.449 ± 0.024, and −33.0 ± 4.9 mV, respectively, with 90.4 ± 0.8% complexation efficiency and 62.3 ± 0.2% drug loading; in vivo studies using a BALB/c mouse skin infection model revealed that nanoplexes reduced MRSA burden by 2.3−fold compared to bare vancomycin [ 93 ]. Liposomal vancomycin topical formulations have also produced similar results against MRSA, reconfirming the importance of the formulation for fighting drug−resistant microbia [ 94 ].…”
Section: Asa With Ampsmentioning
confidence: 91%
“…Vancomycin formulated as nanoplexes of the antibiotic with dextran sulfate sodium salt has recently addressed MRSA infections; the size, polydispersity, and zeta potential of the optimized nanoplexes were 84.6 ± 4.3 nm, 0.449 ± 0.024, and −33.0 ± 4.9 mV, respectively, with 90.4 ± 0.8% complexation efficiency and 62.3 ± 0.2% drug loading; in vivo studies using a BALB/c mouse skin infection model revealed that nanoplexes reduced MRSA burden by 2.3−fold compared to bare vancomycin [ 93 ]. Liposomal vancomycin topical formulations have also produced similar results against MRSA, reconfirming the importance of the formulation for fighting drug−resistant microbia [ 94 ].…”
Section: Asa With Ampsmentioning
confidence: 91%
“…Similarly, in the study conducted in 2019, van's liposome van. In a study conducted in 2019, it was also stated that vancomycin is more toxic than liposome-loaded vancomycin [29]. Cell viability incubated with 25 µg/ml Alg-Van Gels was 87.15±4.14, while it was 82.39±4.37 at 200 µg/ml (P>0.05).…”
Section: Cytotoxicitymentioning
confidence: 96%
“…Vancomycin has been encapsulated in various types of liposomes [ 17 , 18 ] using various methods of encapsulation [ 18 ] for the purpose of meeting various objectives [ 19 , 20 , 21 , 22 ]. These objectives include increasing its antimicrobial efficacy using fusogenic liposomes [ 23 ], targeting and enhancing the efficacy of its topical use [ 24 ], and use in pneumonia by increased deposition in lungs [ 25 , 26 ], etc. A coating of polyethylene glycol (PEG) provides the liposome particle a corona by which it can go undetected by the body’s defense mechanism via the reticuloendothelial system (RES), allowing circulation in the body for a greater amount of time compared to conventional liposomes that lack PEGylation.…”
Section: Introductionmentioning
confidence: 99%